The Impact of Reforms in the Field of Labour Taxation on Dynamics of Informal Employment in Russia - D. V. Nekipelova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the interconnection between reforms in the system of labour taxation, included in the income tax of individuals and contributions to social insurance and welfare of citizens and the dynamics of informal employment in Russia, calculated by human resource balance. The analysis leaned on the hypothesis about the exceptional impact of tax burden on the rate of informal employment, which in case of rising tax burden on the official sector acts as a tool of cutting costs for business and becomes a part of survival strategy for the population. In order to get the most reliable empiric data the dynamics of informal employment was calculated by human resource balance as a difference between the total number of those employed in economy and the average membership of the corporate sector. By the comparative analysis of labour taxation systems of OESR country-members the following conclusion was drawn: the current characteristics of the national system of taxation in the field of employment together with unfavourable factors of the home labour market push both employers and employees to informal employment. The retrospective analysis of results of the most important taxation initiatives in reducing and raising the tax burden on labour showed that resolving the problem is possible in the field of strengthening the labour market institutions together with the development and adoption of the long-term taxation policy in respect of citizens’ income of employment.